2015
DOI: 10.1136/bmj.h521
|View full text |Cite
|
Sign up to set email alerts
|

Stage III pancreatic cancer and the role of irreversible electroporation

Abstract: About a third of patients with pancreatic cancer present with locally advanced disease that is not amenable to resection. Because these patients have localized disease, conventional ablative therapies (thermal ablation and cryoablation) have the potential to be beneficial, but their use is inherently limited in the pancreas. These limitations could be overcome by irreversible electroporation-a novel, non-thermal ablative method that is gaining popularity for the treatment of many soft tissue tumors, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 90 publications
0
30
0
Order By: Relevance
“…Arrhythmias are contraindicated because the pulses are unable to be synchronized with the R-waves [9]. Metallic stents may conduct the electrical current and deflect the energy causing damage to surrounding structures or incomplete ablation [13]. Pre-operative removal of these stents is advisable.…”
Section: Discussionmentioning
confidence: 99%
“…Arrhythmias are contraindicated because the pulses are unable to be synchronized with the R-waves [9]. Metallic stents may conduct the electrical current and deflect the energy causing damage to surrounding structures or incomplete ablation [13]. Pre-operative removal of these stents is advisable.…”
Section: Discussionmentioning
confidence: 99%
“…Induction chemotherapy of either FOLFIRINOX or GEMbased chemotherapy was used for a duration of 4 months (totaling 3 cycles of GEM-based chemotherapy or 4-6 cycles of FOLFIRINOX-based chemotherapy), which was in accordance with previous studies (12,13). The same line of chemotherapy was performed 7-14 days after IRE treatment.…”
Section: Treatment Proceduresmentioning
confidence: 99%
“…The safety of IRE in the pancreas has been demonstrated in multiple studies. 8,[19][20][21] An initial experience with IRE for LAPC demonstrated statistically significant improvements in local progression-free survival (PFS), distant PFS, and OS. 22 In the largest series of patients receiving pancreatic IRE for margin accentuation and in situ treatment for LAPC, Martin et al demonstrated a median OS of 24.9 months from the time of diagnosis, median local PFS of 10.7 months, and median distant PFS of 16.8 months.…”
Section: Irreversible Electroporation Outcomesmentioning
confidence: 99%